Perancangan Kontrol Fuzzy Adaptif Pada Sistem Kontrol Kecepatan Stasioner Mesin Bensin - Muhammad Fajri Nur Reimansyah; Aris Triwiyatno; Budi Setiyono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2014)
Idle speed control has been a classical problem in automotive control. The problem of idle speed control is to maintain the engine speed at a predetermined value (set-point) in the presence of various external torque such as air conditioner or power steering usage. Good idle speed control not only can reduce fuel consumption and emissions but also improve combustion stability. This study was conducted by simulating gasoline engine performance with various changes in external torque parameter using computational software. Control of idle speed with various changes in external torque was done using fuzzy control with adaptive mechanism on its parameters. System testing was done by providing an external torque changes using various step signals and random signal. The test results show that controlling system with adaptive fuzzy is able to keep idle speed at a predetermined value. Testing the system with adaptive fuzzy control produces smaller IAE value (59.19) than the fuzzy control without adaptation process (62.41).